2020
DOI: 10.1099/mgen.0.000419
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired infection caused by the uncommon hypervirulent Klebsiella pneumoniae ST66-K2 lineage

Abstract: Klebsiella pneumoniae (Kp) reference strain Kp52.145 is widely used in experimental Klebsiella pathophysiology. Since 1935, only one other strain of the same sublineage (sequence type ST66, capsular serotype K2) was isolated (AJ210, Australia). Here, we describe a community-acquired invasive infection caused by a ST66-K2 Kp strain in France. Four hypermucoviscous Kp isolates responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…The target microorganism in our study was the hypervirulent Klebsiella pneumoniae strain, 52145 [ 51 ], a reference strain of serotype O1:K2 that has been thoroughly analyzed since its first isolation [ 2 , 56 , 57 ]. This strain belonged to the ST66-K2 lineage [ 17 ], which was recently reported to cause community-acquired infections [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The target microorganism in our study was the hypervirulent Klebsiella pneumoniae strain, 52145 [ 51 ], a reference strain of serotype O1:K2 that has been thoroughly analyzed since its first isolation [ 2 , 56 , 57 ]. This strain belonged to the ST66-K2 lineage [ 17 ], which was recently reported to cause community-acquired infections [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no chromosomal bla SHV was detected in the chromosome (CP052386.1) of K. pneumoniae strain C17KP0055 from South-Korea, which is highly similar to the strain in our study. This is rare but absence of SHV has previously been reported in some K. pneumoniae strains [49,50].…”
Section: Discussionmentioning
confidence: 78%
“…Rodrigues et al recently described the first ST66-K2 isolate identified in Europe; this isolate was obtained from blood and urine samples of a patient infected with HIV in 2018 in France [ 11 ]. Phylogenetic analysis revealed a relationship to the three known ST66-K2 isolates: (I) SB5881 isolated in 2018 from France [ 11 ], (II) AJ210 isolated in 2010 from Australia [ 18 ], and (III) “ancestral” reference Kp52.145 detected in 1935 in Indonesia ( Figure 2 ) [ 11 , 19 ]. However, 18-0005 was more closely related to SB5881 (84 SNPs) than to AJ210 (152 SNPs) or Kp52.145 (409 SNPs).…”
Section: Resultsmentioning
confidence: 99%
“…While the majority of serotype K1 isolates belong to CG23, serotype K2 isolates are genetically more diverse [ 9 ]. The first completely sequenced hvKp strains were NTUH-K2044 (CG23, serotype K1) and Kp52.145 (CG66, serotype K2); both have been used as reference isolates for comparative studies [ 10 , 11 ]. However, clinical isolates of the lineage CG66-K2 (related to Kp52.145) have only been documented twice worldwide [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation